Prevalence of gestational diabetes mellitus and selected risk factors among pregnant women in Hospital Universiti Sains Malaysia - Fong, Ong Ming (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia., 2021)
The current prevalence of Gestational Diabetes Mellitus (GDM) was globally increasing included in Malaysia, and its associated risk factors were not adequately studied. It is important in the planning of preventive measures of GDM effectively thus, lowering the prevalence of GDM in Malaysia. A cross-sectional study was conducted in Obstetrics and Gynecology Clinic, Hospital Universiti Sains Malaysia from December 2020 to February 2021. A total of 89 respondents was purposively selected and the data was collected using a structured self-administered questionnaire. The mean age of respondents was 32 years old (SD= 5.8), with age ranging between 21 to 46 years old. Pearson’s Chi-Square or Fisher’s exact test was used to determine the association of selected risk factors to the prevalence of GDM. Results showed that the prevalence of GDM was 33.7% and majority of them were on diet control. The results also showed sociodemographic characteristics were not statistically significant associated with the prevalence of GDM. The study also revealed there was no significant association between BMI, gestational status, family history of diabetes mellitus, knowledge of women about risk factors of GDM, dietary pattern and physical activities with the prevalence of GDM except the past history of GDM (p=0.016) among the women in Obstetrics and Gynecology Clinic, Hospital Universiti Sains Malaysia. The conclusion is that the prevalence of GDM is high and past history of GDM is associated with GDM. Risk factors that may cause GDM should be recognized to allow early prevention interventions to decrease the prevalence and complications of GDM.